Oral History Interview with Ruth Chiang: Growing SMU - CHIANG, Ruth (Institutional Knowledge at Singapore Management University, 2015)
The interview covered: first involvement with SMU, first batch of SMU students, student creed, CIRCLE values, student community service, finishing touch program, career services including OnTrac, internship, graduate employment service, Dato’ Kho Hui Meng Career Centre. Biography: Director of the Office of Student Life and the Office of Career Services, SMU, 2000-2015 Ruth has a Master Degree in Communications Management from the University of South Australia; a graduate Diploma in Business Administration from NUS and a Bachelor of Arts in Sociology and Economics from Singapore University. She is also an accredited administrator of personality inventories like MBTI, DISC, MAPP, Proscan, Strong’s Interest, CareerLeader, Career Mastery as well as Career Coaching. She is also a trained life and executive coach and a council member with SE CDC for about 15 years. Prior to joining SMU, Ruth worked at People’s Association, served with 4 CEOs and 3 Deputy Chairmen (including then Deputy Prime Minister Wong Kan Seng), and several Members of Parliament. She was in charge of personnel and finance, internal audit, and CDC Planning and Development and OBS corporate relations and administration. Some of her achievements included the takeover and rebuilding of Outward Bound School (OBS) from Ministry of Defence, the organization of the 1st women’s conference on 12 March 2000 for more than 1,000 participants and the 1st CDC Seminar on 19 March 2000 launched by then PM Goh Chok Tong. Ruth was a member of the Millennium Swing Organizing Committee with about 500,000 people celebrating the dawn of the 21st Century at Orchard Road.